Pentingnya Motivasi Belajar dalam Meningkatkan Hasil Pembelajaran Melalui Peningkatan Kualitas Pengajaran - Fauziah Nasution; Yusnita Rani Hasibuan; Eliyanti Manurung; Eka Wahyuni (Prodi Perpustakaan dan Sains Informasi, 2022)
Motivation is the driving force that transforms the energy within a person into concrete actions to achieve certain goals. Some goals in the form of educational activities one of which is learning, learning should have a sense of comfort, seriousness and enthusiasm, so that learning objectives are achieved properly in accordance with the national education system. This is a sign that a task is not relevant to his needs. Anything that appeals to others may not appeal to certain people unless it satisfies their needs. Learning is an interaction between students, learning resources and the environment to acquire new knowledge and skills. Three learning keywords are so important, namely: interactive process, resources and environment as well as new knowledge and skills. Therefore, motivation to learn to teach is a unit that must be mastered by each individual student. This study aims to find out how the relationship between motivation, learning, and teaching. This study uses descriptive qualitative research methods with data collection methods through literature review taken through journals and books related to research. So it can be concluded that motivation, learning and teaching have a close relationship to the success of students.